2014
DOI: 10.1371/journal.pone.0110889
|View full text |Cite
|
Sign up to set email alerts
|

Fixational Eye Movement Correction of Blink-Induced Gaze Position Errors

Abstract: Our eyes move continuously. Even when we attempt to fix our gaze, we produce “fixational” eye movements including microsaccades, drift and tremor. The potential role of microsaccades versus drifts in the control of eye position has been debated for decades and remains in question today. Here we set out to determine the corrective functions of microsaccades and drifts on gaze-position errors due to blinks in non-human primates (Macaca mulatta) and humans. Our results show that blinks contribute to the instabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…This eye movement is not due to mechanical forces of the eyelid on the orbit, but due to an active neural signal [14,15]. Like every motor action, this eye movement is subject to noise [2,16]. Retinal position displacements introduced by blink-induced gaze shifts are generally not perceived as illusory object motion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This eye movement is not due to mechanical forces of the eyelid on the orbit, but due to an active neural signal [14,15]. Like every motor action, this eye movement is subject to noise [2,16]. Retinal position displacements introduced by blink-induced gaze shifts are generally not perceived as illusory object motion.…”
Section: Resultsmentioning
confidence: 99%
“…Microsaccades occurring after a blink have been shown to partially correct for blink-induced gaze instability [2], but the adaptive eye movement reported here is anticipatory and occurs during the blink. In a recent study, Khazali et al [16] showed that one function of blink-related eye movements is to reset the torsional position of the eye.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…25,26 Over a longer time scale, slow drifts, oscillatory eye movements, vergence efforts, and blink-induced position errors come into play. 2,27 Saccades are also a major source of variability in ocular deviation because the act of making a saccade contributes to disconjugacy and position drift (Figure 5). Saccadic disconjugacy has been documented previously in humans and monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, with each microsaccade, the retinal image of a stationary object is shifted to a new location, perhaps several dozen to several hundred photoreceptor widths away (Costela, McCamy, Macknik, Otero-Millan, & Martinez-Conde, 2013; Martinez-Conde, Macknik, Troncoso, & Dyar, 2006; Martinez-Conde, Macknik, Troncoso, & Hubel, 2009; McCamy, Macknik, & Martinez-Conde, 2014; McCamy et al, 2012; Troncoso, Macknik, & Martinez-Conde, 2008), causing the retinal image to land on an unstimulated region of photoreceptors and keeping the image ‘refreshed’. Microsaccades also appear to sharpen the perception of edges (Donner & Hemila, 2007), improve spatial resolution (Ko, Poletti, & Rucci, 2010), correct fixation errors related to eye blinks (Costela et al, 2014), enhance visibility for peripheral and parafoveal visual targets (Costela et al, 2013; Martinez-Conde et al, 2006; McCamy et al, 2012), and sample informative regions of natural scenes (McCamy, Macknik, & Martinez-Conde, 2014). Microsaccade dynamics may even offer insight into such states as the viewers attentional level (Engbert & Kliegl, 2003; Yuval-Greenberg, Merriam, & Heeger, 2014) and fatigue (Di Stasi et al, 2013), as well as indicating target detection and the cognitive demands of the task (Otero-Millan, Troncoso, Macknik, Serrano-Pedraza, & Martinez-Conde, 2008; Siegenthaler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%